The Rootstock Regulates Microbiome Diversity in Root and Rhizosphere Compartments of Vitis vinifera Cultivar Lambrusco - D’Amico, Federica; Candela, Marco; Turroni, Silvia; Biagi, Elena; Brigidi, Patrizia; Bega, Alessia; Vancini, Davide; Rampelli, Simone (Frontiers in Microbiology, 2018)
Plants belonging to Vitis vinifera varieties are usually grafted on different rootstocks to enhance the plant defenses against pathogens and increase productivity under harsh environmental conditions. Particularly, in Emilia-Romagna region (Italy), Vitis vinifera cultivar Lambrusco can be grafted on a hybrid of V. berlandieri × V. riparia (5BB) or V. berlandieri × V. rupestris (1103P). However, the latter shows potassium absorption problems, with a consequent reduction in grapevine production. Since it has recently been demonstrated that the rootstock has the potential to select for different microorganisms at the root-soil interface, here we hypothesized that the potassium deficiency of 1103P could be partially accounted for by the peculiarities of the rootstock microbiome. We thus employed 16S rRNA sequencing to compare root and rhizosphere microbiomes in plants of V. vinifera cultivar Lambrusco grafted on the two aforementioned rootstocks. According to our findings, 1103P shows a reduced diversity in root and rhizosphere microbiomes, including members of potassium-solubilizing microorganisms, possibly explaining the inadequate potassium absorption of this hybrid. Besides confirming the importance of the rootstock as a determinant of the composition of plant microbiomes, our data indicate the relevance of rootstock-selected microbiomes as possible regulators of potassium absorption by V. vinifera.